2012
DOI: 10.5455/msm.2012.24.171-177
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Factor as Breast Cancer Risks

Abstract: Background:Numerous studies have observed risk factors for breast cancer. We investigated the association between quality life factors as breast cancer risks in a case-control study in industrial Zenica- Doboj Canton in Bosnia and Herzegovina.Methods:The case-control study was included 200 women, 100 without (control subjects) and 100 women with diagnosed breast cancer. We used questionnaires about breast cancer risks“ as study tool. Logistic regression was used to compute odds ratios (ORs) and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…If the grandmother had cancer increases the relative risk for nearly twice times more compared to the subjects without family predisposition (OR = 2.2), but risk is 4 times higher if the breast cancer had a distant cousin (OR = 4.4) It is known that obesity and physical is associated with increased incidence of breast cancer [1,11,24]. A study conducted in Sweden and Finland has shown that obesity in older women (median age 56, BMI> 30) increases the risk of breast cancer in younger women (median age 30) and shows inversion [3]. Our study patients were mostly in a group of overweight, 50% of them, obese 21% and 70% of them do not practiced physical training in the total sample [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the grandmother had cancer increases the relative risk for nearly twice times more compared to the subjects without family predisposition (OR = 2.2), but risk is 4 times higher if the breast cancer had a distant cousin (OR = 4.4) It is known that obesity and physical is associated with increased incidence of breast cancer [1,11,24]. A study conducted in Sweden and Finland has shown that obesity in older women (median age 56, BMI> 30) increases the risk of breast cancer in younger women (median age 30) and shows inversion [3]. Our study patients were mostly in a group of overweight, 50% of them, obese 21% and 70% of them do not practiced physical training in the total sample [15].…”
Section: Discussionmentioning
confidence: 99%
“…What do we currently know about the social and environmental causes of breast cancer? Although it is considered that the development of breast cancer result of the interaction of genetic factors we do not yet know aetiology of breast cancer [1][2][3]. From 85 to 90% of cases remains unknown, although it is believed that environmental factors play a leading role and predicted breast carcinoma in 75% cases of cancer [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…If the grandmother had cancer increases the relative risk for nearly twice times more compared to the subjects without family predisposition (OR = 2.2), but risk is 4 times higher if the breast cancer had a distant cousin (OR = 4.4) It is known that obesity and physical is associated with increased incidence of breast cancer [1,11,24]. A study conducted in Sweden and Finland has shown that obesity in older women (median age 56, BMI> 30) increases the risk of breast cancer in younger women (median age 30) and shows inversion [3]. Our study patients were mostly in a group of overweight, 50% of them, obese 21% and 70% of them do not practiced physical training in the total sample [15].…”
Section: Discussionmentioning
confidence: 99%
“…Filling in the questionnaire met the requirements for ethical anonymity. The questionnaire contains a group questions about individual, social and demographic data (such as age, education, main lifetime occupation, employment, place of living, wealth status, satisfaction of financial situation, physical activity: is she active, and how much); a group questions related breast cancer history within a familiar history of breast cancer (such as arrival time of menarche and menopause, childbirth history, breast fed history, contraception use history, hormone therapy history, data of hormone replacement therapy, previous breast diseases: cystic formation, atypical hyperplasia, carcinoma in situ, previous forms of carcinoma); a group questions related to exposure to occupational and environmental risks, how much and for how long (stress, chlorinated compounds, mercury, PAHs and other vapours); questions of smoking habits and alcohol consumption (how much and for how long) [3,[6][7][8]22].…”
Section: Questionnaire Items and Measuresmentioning
confidence: 99%
See 1 more Smart Citation